2013
DOI: 10.1089/sur.2012.183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Storage and Bedside Filtered Leukocyte-Depleted Blood Transfusions on Infective Morbidity after Colorectal Resection: A Single-Center Analysis of 437 Patients

Abstract: Leukocyte-depleted blood transfusions and, in particular, bedside-filtered blood have a significant negative effect on infectious complications after colorectal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Our data indicate that blood transfusion has no effect on the development of SSI in liver surgery. However, we cannot draw any conclusion on the effect of the type of transfused blood, as described in colorectal surgery (25), and suggested by Okabayashi et al (15) because only one of our patients received leukocyte-depleted blood.…”
Section: Discussionmentioning
confidence: 74%
“…Our data indicate that blood transfusion has no effect on the development of SSI in liver surgery. However, we cannot draw any conclusion on the effect of the type of transfused blood, as described in colorectal surgery (25), and suggested by Okabayashi et al (15) because only one of our patients received leukocyte-depleted blood.…”
Section: Discussionmentioning
confidence: 74%
“…An allergic reaction was found in 75% of the studies analyzed 19,20,[44][45][46] , but it was not considered an outcome in this review because leukoreduction is not an indication for preventing it since its pathophysiology is different from that of FNHTRs and is related to the presence of anti-IgE antibodies in the receptor 4 . Two studies 21,25 analyzed the presence of postsurgical infection for immunomodulation, but one study showed that surgery had a high potential for contamination (colorectal resection) 21 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the risk of selection bias is important in studies that analyzed data from before and after the adoption of pre-storage leukoreduction in all transfusions since the sample of patients who received transfusions with post-storage leukoreduction was more restricted and had a higher risk of TR, as already mentioned 20,43,45,46 . The answers to question 6 were unclear in four studies 19,21,43,45 , as there was no report on the follow-up time for evaluating the outcomes. Question 5 was considered not applicable to the quasi-experimental studies of interest for this review because TRs are only transfusional if they occur after the intervention (transfusion), and there is no reason to evaluate them before transfusions.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations